Nonlinear Prices and the Regulated Firm - Srinagesh, Padmanabhan (Quarterly Journal of Economics, 1986)
This paper examines the problem of a regulated utility that sells output according to a nonlinear price schedule. Three results are obtained. First, rate-of-return regulation lowers the price schedule charged by the firm along its entire length. Second, some units of output will always be sold at a marginal price below true marginal cost. Third, a move from linear to nonlinear prices at a given fair rate-of-return can lead to an unambiguous increase in welfare.